Potential of Finger Millet Indigenous Rhizobacterium Pseudomonas sp. MSSRFD41 in Blast Disease Management—Growth Promotion and Compatibility With the Resident Rhizomicrobiome - Sekar, Jegan; Raju, Kathiravan; Duraisamy, Purushothaman; Ramalingam Vaiyapuri, Prabavathy (Frontiers in Microbiology, 2018)
Finger millet [Eleusine coracona (L). Gaertner] “Ragi” is a nutri-cereal with potential health benefits, and is utilized solely for human consumption in semi-arid regions of Asia and Africa. It is highly vulnerable to blast disease caused by Pyricularia grisea, resulting in 50–100% yield loss. Chemical fungicides are used for the management of blast disease, but with great safety concern. Alternatively, bioinoculants are widely used in promoting seedling efficiency, plant biomass, and disease control. Little is known about the impact of introduced indigenous beneficial rhizobacteria on the rhizosphere microbiota and growth promotion in finger millet. Strain MSSRFD41 exhibited a 22.35 mm zone of inhibition against P. grisea, produces antifungal metabolites, siderophores, hydrolytic enzymes, and IAA, and solubilizes phosphate. Environmental SEM analysis indicated the potential of MSSRFD41 to inhibit the growth of P. grisea by affecting cellular functions, which caused deformation in fungal hyphae. Bioprimed finger millet seeds exhibited significantly higher levels of germination, seedling vigor index, and enhanced shoot and root length compared to control seeds. Cross streaking and RAPD analysis showed that MSSRFD41 is compatible with different groups of rhizobacteria and survived in the rhizosphere. In addition, PLFA analysis revealed no significant difference in microbial biomass between the treated and control rhizosphere samples. Field trials showed that MSSRFD41 treatment significantly reduced blast infestation and enhanced plant growth compared to other treatments. A liquid formulated MSSRFD41 product maintained shelf life at an average of 108 CFU ml−1 over 150 days of storage at 25°C. Overall, results from this study demonstrated that Pseudomonas sp. MSSRFD41, an indigenous rhizobacterial strain, is an alternative, effective, and sustainable resource for the management of P. grisea infestation and growth promotion of finger millet.